Macro-economic determinants, maternal and infant SDG targets in Nigeria: Correlation and predictive modeling - Adegoke, Yetunde Oluranti; Mbonigaba, Josue; George, Gavin (Frontiers in Public Health, 2022)
Objectives Unambiguously, Nigeria is off-track in achieving the health-related SDGs. Consequentially, this study aligns with SDG 3 which calls for “good health and wellbeing for people by ensuring healthy lives and promoting wellbeing for all at all ages”. This article examines the combined effect of health expenditure and other key macro-economic factors on health indices such as maternal and newborn and child mortality in Nigeria. Contrary to existing literature, we formulated a model that predicts the level of macro-economic determinants needed to achieve the SDG targets for maternal and newborn and child mortality in Nigeria by 2030. Methodology The study used Autoregressive Distributed Lag (ARDL), which is usually used for large T models. The study period spans from 1995 to 2020. Results We found a significant negative relationship between health outcomes and macro-economic determinants namely, household consumption, total health expenditure, and gross fixed capital while we determined a significant positive relationship between health outcomes and unemployment. Our findings are further supported by out-of-sample forecast results suggesting a reduction in unemployment to 1.84 percent and an increase in health expenditure, gross fixed capital, household consumption, control of corruption to 1,818.87 billon (naira), 94.46 billion (naira), 3.2 percent, and −4.2 percent respectively to achieve SDG health targets in Nigeria by 2030. Policy implication The outcome of this result will give the Nigerian government and stakeholders a deeper understanding of the workings of the macro-economic factors, concerning health performance and will help position Nigeria, and other SSA countries by extension, toward reducing maternal mortality to 70 per 100,000 and newborn and child mortality to 25 per 1,000 births by 2030. The African leaders should consider passing into law the need for improvement in macro-economic factors for better health in Africa. We also recommend that the Nigerian government should steadily increase health expenditure to reach and move beyond the forecast level for improvement in maternal and infant mortality, given the present low and unimpressive funding for the health sector in the country.